High-yield preparation method of polymeric nitrogen material and polymeric nitrogen material
By mixing the azide precursor, carbon nanotube or carbon nanotube membrane with liquid under a low vacuum environment, heating, insulation and cooling, the problems of high pressure, low yield and instability of cg-PN material synthesis in the prior art are solved, and the preparation of cg-PN material with high yield and stable at normal pressure is achieved, with higher energy density and application potential.
Patent Information
- Application Number
- CN202411381604.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The method of synthesizing polymeric nitrogen (cg-PN) materials in the prior art requires high pressure, harsh conditions and low yields, and the synthetic cg-PN materials cannot exist stably under normal pressure.
By mixing the azide precursor, carbon nanotube or carbon nanotube film with a liquid, heating, insulation and cooling under a low vacuum environment, a high yield polymer nitrogen material is prepared.
The preparation of cg-PN materials at high yields under normal pressure is achieved, which reduces the difficulty of synthesis, and the prepared materials are stable at normal temperature and pressure, with higher energy density and application potential.
Smart Images

Figure CN119706755A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energetic materials, and in particular relates to a high-yield preparation method of a polymerized nitrogen material and the polymerized nitrogen material. Background Art
[0002] The energy density of traditional energetic materials has gradually approached its theoretical limit, making it difficult to meet the growing demand for energy density in practical applications. Due to its unique electronic structure, nitrogen has the potential to form high-energy density materials. The bond energy of the N≡N triple bond is 954 kJ / mol, and the bond energy of the NN single bond is 160 kJ / mol. Polymeric nitrogen (hereinafter referred to as cg-PN) materials formed by NN single bonds release huge energy when decomposed into gaseous nitrogen with N≡N triple bonds. cg-PN materials are expected to play an important role in practical applications. At present, the synthesis of cg-PN usually requires extreme conditions such as high temperature and high pressure. Eremets et al. reported the successful synthesis of cg-PN using molecular nitrogen as a precursor, a pressure of about 110 GPa, and a temperature of 2000 K. Unfortunately, cg-PN cannot exist stably at normal pressure.
[0003] While cg-PN has been studied in detail theoretically in recent years, experimental studies have been rare. The synthesis of cg-PN typically requires extreme conditions, such as high temperature and pressure, placing high demands on experimental equipment and techniques. Producing cg-PN at higher yields under ambient pressure remains an urgent challenge. Summary of the Invention
[0004] In view of the above analysis, the present invention aims to provide a high-yield preparation method of a polymeric nitrogen material and a polymeric nitrogen material to solve one of the following technical problems: (1) The method for synthesizing cg-PN in the prior art requires a high pressure and harsh conditions, which are difficult to achieve; (2) The content of cg-PN synthesized in the prior art is low; (3) The cg-PN synthesized in the prior art cannot exist stably under normal pressure.
[0005] The purpose of the present invention is mainly achieved through the following technical solutions:
[0006] The present invention provides a high-yield preparation method for a polymerized nitrogen material, comprising: mixing an azide precursor, carbon nanotubes or a carbon nanotube film with a liquid to obtain a mixture; heating, maintaining the mixture, and cooling the mixture under a low vacuum environment to obtain a polymerized nitrogen material (hereinafter referred to as a cg-PN material); the mass of the carbon nanotubes or the carbon nanotube film is 1% to 100% of the azide precursor.
[0007] Furthermore, the carbon nanotubes include one or more of carboxylated single-walled carbon nanotubes, single-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, amino-modified multi-walled carbon nanotubes, graphitized multi-walled carbon nanotubes and graphitized carboxylated multi-walled carbon nanotubes.
[0008] Furthermore, the preparation method includes: mixing an azide precursor, carbon nanotubes and a liquid to obtain a mixed liquid, and heating, keeping the mixed liquid warm and cooling the mixed liquid under a low vacuum environment to obtain a polymerized nitrogen material.
[0009] Furthermore, the preparation method includes: mixing an azide precursor with a liquid to obtain a mixed liquid, spreading a carbon nanotube film in a container, placing the mixed liquid on the carbon nanotube film, and heating, keeping the container and the material in the container under a low vacuum environment to obtain a polymerized nitrogen material.
[0010] Furthermore, the heating rate is 2 to 10° C. / min.
[0011] Furthermore, the cooling rate is 50-200°C / min.
[0012] Furthermore, the azide precursor includes one or more of NH4N3, NaN3, LiN3 and KN3.
[0013] Furthermore, the liquid includes water, alcohol, acid solution or alkaline solution.
[0014] Furthermore, the mass of the liquid is more than 40% of the azide precursor.
[0015] Furthermore, the acid solution is one or more of hydrochloric acid solution and acetic acid solution.
[0016] The present invention also provides a polymeric nitrogen material, which is prepared by the above-mentioned preparation method.
[0017] Compared with the prior art, the present invention can achieve at least one of the following technical effects:
[0018] 1) The high-yield preparation method of the present invention promotes the decomposition of the azide precursor and its participation in the reaction to synthesize the polymerized nitrogen material by adding a liquid and carbon nanotubes or carbon nanotube films. This breaks through the high pressure condition required for the traditional method of synthesizing cg-PN materials, greatly reduces the difficulty of synthesis, and becomes a new method for synthesizing cg-PN materials.
[0019] 2) The high-yield preparation method of the polymeric nitrogen material of the present invention is very simple and easy to implement, which greatly reduces the experimental difficulty.
[0020] 3) The high-yield preparation method of the present invention has a higher yield of the polymerized nitrogen material obtained, and the polymerized nitrogen material prepared by this method can maintain its stability at room temperature and pressure, breaking through the limitation of traditional technology that polymerized cg-PN materials can only exist under high pressure. This feature makes this material promising to open up new application prospects in the fields of energy storage, high energy density energetic materials, etc.
[0021] Other features and advantages of the present invention will be described in the following description, and in part they may become apparent from the description or may be understood through implementation of the present invention. The purposes and other advantages of the present invention may be realized and obtained through the structures particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings are only for purposes of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference numerals designate like components throughout the drawings.
[0023] Figure 1 This is the Raman spectrum of the cg-PN material of Example 1 of the present invention;
[0024] Figure 2 This is the Raman spectrum of the cg-PN material of Example 2 of the present invention;
[0025] Figure 3 This is the Raman spectrum of the cg-PN material of Example 3 of the present invention;
[0026] Figure 4 This is the Raman spectrum of the cg-PN material of Example 4 of the present invention;
[0027] Figure 5 This is the Raman spectrum of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The following is a further detailed description of a high-yield preparation method of a polymerized nitrogen material and the polymerized nitrogen material in conjunction with specific examples. These examples are only for comparison and explanation purposes, and the present invention is not limited to these examples.
[0029] The present invention provides a high-yield preparation method for a polymerized nitrogen material, comprising: mixing an azide precursor, carbon nanotubes or a carbon nanotube film with a liquid to obtain a mixture; heating the mixture to a holding temperature, holding the temperature, and cooling the mixture under a low vacuum environment to obtain a cg-PN material.
[0030] Specifically, the azide precursor includes one or more of NH4N3, NaN3, LiN3 and KN3.
[0031] Specifically, the carbon nanotubes include one or more of carboxylated single-walled carbon nanotubes, single-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, amino-modified multi-walled carbon nanotubes, graphitized multi-walled carbon nanotubes and graphitized carboxylated multi-walled carbon nanotubes.
[0032] Specifically, considering that too much carbon nanotube mass will result in a low relative content of cg-PN in the product, which is not conducive to fully realizing its energy performance, while too little will reduce the conversion rate of cg-PN, which is not conducive to increasing cg-PN production. Therefore, the mass of the carbon nanotubes or carbon nanotube film is controlled to be 1% to 100% of the azide precursor. For example, the mass of the carbon nanotube film can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% of the azide precursor.
[0033] Specifically, the liquid includes water, alcohol, acid solution or alkaline solution, etc.
[0034] Specifically, the acid solution may be one or more of a hydrochloric acid solution and an acetic acid solution.
[0035] Specifically, the concentration of the acid solution may be 0.01 to 0.1 mol / L.
[0036] Specifically, the alkaline solution may be one or more of a calcium hydroxide solution and a sodium hydroxide solution.
[0037] Specifically, the concentration of the alkaline solution may be 0.1 to 5 mol / L.
[0038] Considering that excessive liquid mass makes vacuuming difficult, while too little liquid mass prevents complete dissolution of the azide precursor, the liquid mass is controlled to be at least 40% of the azide precursor mass. Preferably, the mass ratio of liquid to azide precursor is 4-5:1-2.
[0039] Specifically, the vacuum degree of the low vacuum environment is 0 to 200 Pa, for example, 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 120 Pa, 140 Pa, 160 Pa, 180 Pa, and 200 Pa.
[0040] Specifically, the mixture is heated to 70-350° C., kept at this temperature for 3-24 hours, and then cooled to obtain the cg-PN material.
[0041] Specifically, when the azide precursor is NH4N3, the holding temperature is 70-90°C, for example, 75°C, 80°C, or 85°C.
[0042] Specifically, when the azide precursor is LiN3, the holding temperature is 90-105°C, for example, 95°C, 100°C, or 105°C.
[0043] Specifically, when the azide precursor is NaN3, the holding temperature is 200-280°C, for example, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, or 270°C.
[0044] Specifically, when the azide precursor is KN3, the holding temperature is 250-350°C, for example, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, or 320°C.
[0045] Considering that a too high heating rate will result in uneven heating of the raw materials, while a too low heating rate will result in incomplete sintering and prolonged sintering time, the heating rate is controlled to be 2-10°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, and 9°C / min.
[0046] Specifically, the preparation method includes: mixing an azide precursor, carbon nanotubes and a liquid to obtain a mixed liquid; and heating, keeping the mixed liquid warm, and cooling the mixed liquid under a low vacuum environment to obtain a cg-PN material.
[0047] Specifically, the preparation method includes: mixing an azide precursor with a liquid to obtain a mixed liquid, spreading a carbon nanotube film in a container, placing the mixed liquid on the carbon nanotube film, and heating, keeping the container and the material in the container and cooling it in a low vacuum environment to obtain a cg-PN material.
[0048] Specifically, the preparation method comprises the following steps:
[0049] S1, weighing azide precursor, carbon nanotubes and liquid;
[0050] S2. placing the weighed raw materials in a container, and then ultrasonicating them in an ultrasonic cleaning apparatus to prepare a suspension;
[0051] S3, placing the suspension in a container (e.g., on a glass sheet, a quartz boat, or a crucible), then placing the container in a tube furnace and evacuating the tube furnace;
[0052] S4. Performing vacuum or flowing gas protection on the sample in the tube furnace, heating it to a holding temperature, and holding the temperature;
[0053] S5. Cooling the tubular furnace to synthesize the cg-PN material.
[0054] Specifically, in the above S2, the container is a glass beaker or a glass weighing bottle.
[0055] Specifically, in S2 above, if the ultrasonication time is too long, the material may be damaged or the solution properties may change, while if it is too short, the raw materials may not be fully mixed. Therefore, the ultrasonication time is controlled to be 8 to 15 minutes, for example, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, or 14 minutes.
[0056] Specifically, in the above S3, the number of vacuuming is 1 to 4 times. The vacuum degree after the vacuuming treatment is 0 to 200 Pa, for example, 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 120 Pa, 140 Pa, 160 Pa, 180 Pa, and 200 Pa.
[0057] Specifically, in the above S4, the vacuum degree is 1 to 5 Pa, for example, 2 Pa, 3 Pa, 4 Pa, or 5 Pa.
[0058] Specifically, in the above S4, the gas includes oxygen, hydrogen, nitrogen, argon or helium, etc., and one or more gases can be introduced.
[0059] Considering that excessive gas flow rates in S4 can lead to excessive pressure in the tube furnace, which is not conducive to the synthesis of cg-PN materials, the gas flow rate is controlled to 1 to 50 standard cubic centimeters. For example, 10 standard cubic centimeters, 20 standard cubic centimeters, 30 standard cubic centimeters, and 40 standard cubic centimeters.
[0060] Specifically, in the above S4, the heating rate of the tube furnace is set to 2 to 10°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, and 9°C / min; the holding time is 3 to 24h, for example, 4h, 5h, 7h, 10h, 12h, 15h, 18h, 20h, and 22h.
[0061] Specifically, in the above S4, a rapid cooling method is generally adopted, and the cooling rate is 50 to 200°C / min, for example, 50°C / min, 100°C / min, 150°C / min, and 200°C / min.
[0062] Alternatively, the preparation method comprises the following steps:
[0063] S1. Weighing azide precursor and liquid; cutting carbon nanotube film;
[0064] S2. placing the weighed azide precursor and liquid in a container and dissolving them to obtain a mixed solution;
[0065] S3, laying the cut carbon nanotube film flat on a container (such as a glass sheet, a quartz boat, or a crucible), dropping the mixed solution on the carbon nanotube film, and then placing the container in a tube furnace and evacuating the tube furnace;
[0066] S4. Performing vacuum or flowing gas protection on the sample in the tube furnace, heating it to a holding temperature, and holding the temperature;
[0067] S5. Cooling the tubular furnace to obtain the cg-PN material.
[0068] Specifically, in the above S2, the container is a glass beaker or a glass weighing bottle.
[0069] Specifically, in the above S3, the number of vacuuming is 1 to 4 times. The vacuum degree after the vacuuming treatment is 0 to 200 Pa, for example, 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 120 Pa, 140 Pa, 160 Pa, 180 Pa, and 200 Pa.
[0070] Specifically, in the above S4, the vacuum degree is 1 to 5 Pa, for example, 2 Pa, 3 Pa, 4 Pa, or 5 Pa.
[0071] Specifically, in the above S4, the gas includes oxygen, hydrogen, nitrogen, argon or helium, etc., and one or more gases can be introduced.
[0072] Considering that excessive gas flow rates in S4 can lead to excessive pressure in the tube furnace, which is not conducive to the synthesis of cg-PN materials, the gas flow rate is controlled to 1 to 50 standard cubic centimeters. For example, 10 standard cubic centimeters, 20 standard cubic centimeters, 30 standard cubic centimeters, and 40 standard cubic centimeters.
[0073] Specifically, in the above S4, the heating rate of the tube furnace is set to 2-10°C / min, and the holding time is 3-24 hours, for example, 4 hours, 5 hours, 7 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, or 22 hours.
[0074] Specifically, in the above S4, a rapid cooling method is generally adopted, and the cooling rate is 50 to 200°C / min, for example, 50°C / min, 100°C / min, 150°C / min, and 200°C / min.
[0075] The present invention also provides a polymeric nitrogen material, which is prepared by the above preparation method.
[0076] The polymeric nitrogen material of the present invention is formed from single N≡N bonds. When decomposed into N≡N triple bonds, it releases enormous amounts of energy, far exceeding the energy release capacity of traditional energetic materials. Furthermore, due to its high energy density and the fact that its decomposition product is nitrogen, it is expected to play an important role in practical applications.
[0077] The polymerized nitrogen material of the present invention realizes charge transfer due to the hybridization of carbon nanotubes and cg-PN during the solubilization process, so that the polymerized nitrogen material can exist stably at room temperature and pressure.
[0078] In the preparation method of the present invention, the decomposition of the azide precursor is promoted by adding liquid and carbon nanotubes or carbon nanotube films, so that the azide precursor participates in the reaction to synthesize the polymerized nitrogen material. This improves the yield of the polymerized nitrogen material and reduces the pressure required for synthesizing the polymerized nitrogen material. Compared with the reaction of synthesizing the polymerized nitrogen material at high temperature and high pressure, the synthesis pressure is greatly reduced, which greatly reduces the difficulty of synthesis, thus becoming a new method for synthesizing the polymerized nitrogen material.
[0079] The polymeric nitrogen material of the present invention is formed from single N-N bonds. When decomposed into nitrogen gas with N≡N triple bonds, it releases enormous amounts of energy, far exceeding the energy release capacity of traditional energetic materials. Furthermore, due to its high energy density and the fact that its decomposition product is nitrogen, it is expected to play an important role in practical applications.
[0080] The high-yield preparation method for polymerized nitrogen materials of the present invention yields a higher yield of cg-PN materials. For example, in a Raman spectrum, the intensity of the Raman peak corresponding to the A mode of the cg-PN material is greater than 16,000, for example, 16,001 to 194,377, which is more than double the characteristic peak of the raw material, for example, 1.36 to 8 times. Furthermore, the cg-PN material of the present invention maintains its stability at room temperature and pressure, breaking through the limitation of conventional polymerized cg-PN materials that they can only survive under high pressure. This feature holds promise for new applications in energy storage, high-energy-density energetic materials, and other fields.
[0081] The embodiments and comparative examples of the present invention use a ReniShaw Raman spectrometer to perform Raman spectrum measurement, with a laser wavelength of 532 nm, a grating of 2400 l / mm, a power output of 0.5% to 5% (for example, 0.5%, 1% or 5%), an integration time of 10 to 120 s (for example, 10 s, 30 s, 60 or 120 s), an integration number of 1 to 4 times (for example, 1 time, 2 times, 3 times or 4 times), and a Raman spectrum test range of 100 to 1500 cm -1 .
[0082] Example 1
[0083] This embodiment provides a high-yield preparation method of a polymerized nitrogen material and a polymerized nitrogen material. The high-yield preparation method includes:
[0084] S1, weighing azide precursor, carbon nanotubes and liquid;
[0085] S2. placing the weighed raw materials in a container, and then ultrasonicating them in an ultrasonic cleaning apparatus to prepare a suspension;
[0086] S3, dropping the suspension onto a glass sheet, then placing the glass sheet in a tube furnace and evacuating the tube furnace;
[0087] S4. Performing operations such as flowing gas protection, heating and heat preservation on the sample in the tube furnace;
[0088] S5. Cooling the tubular furnace to synthesize cg-PN.
[0089] Specifically, in the above S1, KN3 is selected as the azide precursor, and the mass of KN3 is 100 mg.
[0090] Specifically, in the above S1, the carbon nanotubes are carboxylated multi-walled carbon nanotubes with a mass of 7 mg.
[0091] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.
[0092] Specifically, in the above S2, the container is a glass weighing bottle.
[0093] Specifically, in the above S2, the ultrasonic time is 10 minutes.
[0094] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after the vacuuming process is 20Pa.
[0095] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.
[0096] Specifically, in the above S4, the holding temperature is 300°C.
[0097] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the holding time of the sample in the tube furnace is 3 hours.
[0098] Specifically, in the above S5, the cooling rate is 50°C / min.
[0099] The Raman spectrum of the cg-PN material synthesized in this example is shown in FIG. Figure 1 As shown in the Raman spectrum, at 142cm -1 、634cm -1 、1268cm -1 and 1340cm -1 There are 4 obvious strong peaks.- The vibration lattice mode, bending v2 mode and symmetric stretching v1 mode correspond to 142 cm -1 、1268cm -1 and 1340cm -1 The strong peak at wavelength 634cm -1 The Raman peak corresponding to the A mode of the cg-PN material has an intensity of 170740, which is about 6.235 times that of the characteristic peak of the raw material, indicating that the cg-PN material was synthesized using this method.
[0100] Example 2
[0101] This embodiment provides a high-yield preparation method of a polymerized nitrogen material and a polymerized nitrogen material. The steps of this embodiment are substantially the same as those of Example 1, except that:
[0102] In S1, the mass of the carboxylated multi-walled carbon nanotubes is 30 mg.
[0103] The Raman spectrum of the cg-PN material synthesized in this example is shown in FIG. Figure 2 As shown, 634cm -1 The Raman peak corresponding to the A mode of the cg-PN material has an intensity of 194377, which is about 5.701 times that of the characteristic peak of the raw material, indicating that the cg-PN material was synthesized using this method.
[0104] Example 3
[0105] This embodiment provides a high-yield preparation method of a polymerized nitrogen material and a polymerized nitrogen material. The steps of this embodiment are substantially the same as those of Example 1, except that:
[0106] S1, using highly conductive carbon nanotube film;
[0107] S2. placing the weighed azide precursor and liquid in a container and dissolving them to obtain a mixed solution;
[0108] S3. Spread the cut highly conductive carbon nanotube film flatly in a quartz boat, drop the above-mentioned mixed liquid on the highly conductive carbon nanotube film, and then place the quartz boat in a tube furnace and evacuate the tube furnace.
[0109] Specifically, in the above S1, the size of the highly conductive carbon nanotube film is 3 cm×1 cm.
[0110] Specifically, in the above S2, ultrasonic preparation of the suspension is not required.
[0111] The Raman spectrum of the cg-PN material synthesized in this example is shown in FIG. Figure 3 As shown, 634cm -1The intensity of the Raman peak corresponding to the A mode of cg-PN is 139822, which is about 5.501 times that of the characteristic peak of the raw material, indicating that the polymerized cg-PN material was synthesized using this method.
[0112] Example 4
[0113] This embodiment provides a high-yield preparation method of a polymerized nitrogen material and a polymerized nitrogen material. The preparation method includes:
[0114] S1, weighing azide precursor, carbon nanotubes and liquid;
[0115] S2. placing the weighed raw materials in a container, and then ultrasonicating them in an ultrasonic cleaning apparatus to prepare a suspension;
[0116] S3, dropping the suspension onto a quartz boat, then placing the boat in a tube furnace and evacuating the tube furnace;
[0117] S4. Performing operations such as flowing gas protection, heating and heat preservation on the sample in the tube furnace;
[0118] S5. Cooling the tubular furnace to synthesize the cg-PN material.
[0119] Specifically, in the above S1, the azide precursor is selected as NaN3, and the mass of NaN3 is 100 mg.
[0120] Specifically, in the above S1, the carbon nanotubes are carboxylated multi-walled carbon nanotubes with a mass of 7 mg.
[0121] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.
[0122] Specifically, in the above S2, the container is a glass weighing bottle.
[0123] Specifically, in the above S2, the ultrasonic time is 10 minutes.
[0124] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after the vacuuming process is 20Pa.
[0125] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.
[0126] Specifically, in the above S4, the holding temperature is 250°C.
[0127] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the holding time of the sample in the tube furnace is 3 hours.
[0128] Specifically, in the above S5, the cooling rate is 50°C / min.
[0129] The Raman spectrum of the cg-PN material synthesized in this example is shown in FIG. Figure 4 As shown in the Raman spectrum, at 142cm -1 、634cm -1 、1268cm -1 and 1340cm -1 There are 4 obvious strong peaks. - The vibration lattice mode, bending v2 mode and symmetric stretching v1 mode correspond to 142 cm -1 、1268cm -1 and 1340cm -1 The strong peak at wavelength 634cm -1 The intensity of the Raman peak corresponding to the A mode of cg-PN is 16001, which is about 1.695 times that of the characteristic peak of the raw material, indicating that the polymerized cg-PN material was synthesized using this method.
[0130] Example 5
[0131] This embodiment provides a high-yield preparation method of a polymerized nitrogen material and a polymerized nitrogen material. The preparation method includes:
[0132] S1, weighing azide precursor, carbon nanotubes and liquid;
[0133] S2. placing the weighed raw materials in a container, and then ultrasonicating them in an ultrasonic cleaning apparatus to prepare a suspension;
[0134] S3, dropping the suspension onto a quartz boat, then placing the boat in a tube furnace and evacuating the tube furnace;
[0135] S4. Performing operations such as flowing gas protection, heating and heat preservation on the sample in the tube furnace;
[0136] S5. Cooling the tubular furnace to synthesize cg-PN.
[0137] Specifically, in the above S1, the azide precursor is selected as LiN3, and the mass of LiN3 is 100 mg.
[0138] Specifically, in the above S1, the carbon nanotubes are amino-treated multi-walled carbon nanotubes with a mass of 10 mg.
[0139] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.
[0140] Specifically, in the above S2, the container is a glass weighing bottle.
[0141] Specifically, in the above S2, the ultrasonic time is 10 minutes.
[0142] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after the vacuuming process is 20Pa.
[0143] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.
[0144] Specifically, in the above S4, the insulation temperature is 100°C.
[0145] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the holding time is 3 hours.
[0146] Specifically, in the above S5, the cooling rate is 50°C / min.
[0147] This example also carried out the same Raman spectrum test as in Example 1, and the results showed that cg-PN material was synthesized by this method. Due to limited space, we will not list them one by one.
[0148] Example 6
[0149] This embodiment provides a high-yield preparation method of a polymerized nitrogen material and a polymerized nitrogen material. The preparation method includes:
[0150] S1, weighing azide precursor, carbon nanotubes and liquid;
[0151] S2. placing the weighed raw materials in a container, and then ultrasonicating them in an ultrasonic cleaning apparatus to prepare a suspension;
[0152] S3, dropping the suspension onto a quartz boat, then placing the boat in a tube furnace and evacuating the tube furnace;
[0153] S4. Performing operations such as flowing gas protection, heating and heat preservation on the sample in the tube furnace;
[0154] S5. Cooling the tubular furnace to synthesize the cg-PN material.
[0155] Specifically, in the above S1, the azide precursor is NH4N3, and the mass of NH4N3 is 100 mg.
[0156] Specifically, in the above S1, the carbon nanotubes are amino-treated multi-walled carbon nanotubes with a mass of 10 mg.
[0157] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.
[0158] Specifically, in the above S2, the container is a glass weighing bottle.
[0159] Specifically, in the above S2, the ultrasonic time is 10 minutes.
[0160] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after the vacuuming process is 19 Pa.
[0161] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.
[0162] Specifically, in the above S4, the insulation temperature is 80°C.
[0163] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the holding time is 3 hours.
[0164] Specifically, in the above S5, the cooling rate is 50°C / min.
[0165] In this embodiment, this method is used to synthesize polymerized cg-PN materials.
[0166] This example also carried out the same Raman spectrum test as in Example 1, and the results showed that cg-PN material was synthesized by this method. Due to limited space, we will not list them one by one.
[0167] The inventors have conducted a lot of research during the research process, and now list some solutions with poor effects as comparative examples as follows.
[0168] Comparative Example 1
[0169] This comparative example provides a cg-PN material and a preparation method thereof. The steps of this comparative example are substantially the same as those of Example 1, except that:
[0170] S1, no carbon nanotubes added;
[0171] S2. Place the weighed raw materials in a container and dissolve them;
[0172] S3, dropping the above liquid on a glass sheet, then placing the glass sheet in a tube furnace and evacuating the tube furnace;
[0173] Specifically, in the above S2, ultrasonic preparation of the suspension is not required.
[0174] The Raman spectrum of the cg-PN material synthesized in this comparative example is shown in FIG. Figure 5 As shown, 634cm -1 The Raman peak corresponding to the A mode of cg-PN was synthesized using this method, but the peak at 634 cm -1The relative intensity of the A-mode Raman peak corresponding to cg-PN is significantly weaker than that of 634 cm-1 in Examples 1, 2, 3, and 4. -1 The relative intensity of the A-mode Raman peak corresponding to cg-PN indicates that the addition of carbon nanotubes or carbon nanotube films improves the yield of cg-PN synthesis.
[0175] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a polymeric nitrogen material with high yield, characterized in that: include: An azide precursor, carbon nanotubes or carbon nanotube film are mixed with a liquid to obtain a mixture, and the mixture is heated, kept warm and cooled in a low vacuum environment to obtain a polymerized nitrogen material; the mass of the carbon nanotubes or carbon nanotube film is 1% to 100% of the azide precursor.
2. The preparation method according to claim 1, characterized in that: The carbon nanotubes include one or more of carboxylated single-walled carbon nanotubes, single-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, aminated multi-walled carbon nanotubes, graphitized multi-walled carbon nanotubes and graphitized carboxylated multi-walled carbon nanotubes.
3. The preparation method according to claim 1, characterized in that: The preparation method comprises: mixing an azide precursor, carbon nanotubes and a liquid to obtain a mixed liquid, and heating, keeping the temperature and cooling the mixed liquid under a low vacuum environment to obtain a polymerized nitrogen material.
4. The preparation method according to claim 1, characterized in that: The preparation method comprises: mixing an azide precursor with a liquid to obtain a mixed liquid, spreading a carbon nanotube film in a container, placing the mixed liquid on the carbon nanotube film, and heating, keeping warm, and cooling the container and the material in the container under a low vacuum environment to obtain a polymerized nitrogen material.
5. The preparation method according to claim 3 or 4, characterized in that: The heating rate is 2-10°C / min.
6. The preparation method according to claim 3 or 4, characterized in that: The cooling rate is 50-200℃ / min.
7. The preparation method according to claim 1, characterized in that: The azide precursor includes one or more of NH4N3, NaN3, LiN3 and KN3.
8. The preparation method according to claim 1, characterized in that: The liquid includes one or more of water, alcohol, acid solution or alkaline solution.
9. The preparation method according to claim 8, characterized in that: The acid solution is one or more of a hydrochloric acid solution and an acetic acid solution.
10. A polymeric nitrogen material, characterized in that: The polymeric nitrogen material is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Nitrogen polymer and preparation method thereof
CN105540558A
Nitrogen polymer and its production
JP1999043315A
Method for generation of novel materials using nanosecond-pulsed discharge plasma in liquid phase
US20210106968A1